Prevalence and pattern of orthodontic malocclusion in children aged 10–12 years: A systematic review of epidemiological studies. - Hemalatha, Dr.D; Shunmugavelu, Karthik; Kumar S, Santosh (Student's Journal of Health Research Africa, 2026)
Background Malocclusion is a highly prevalent developmental condition in children and contributes to functional, esthetic, and psychosocial concerns. The age group of 10–12 years represents late mixed dentition, a critical phase for orthodontic evaluation and interceptive care. Considerable variation in reported prevalence necessitates focused synthesis within this specific age range. Objective: To systematically evaluate the prevalence and pattern of orthodontic malocclusion in children aged 10–12 years based on epidemiological studies. Materials and methods This systematic review followed PRISMA 2020 guidelines. Electronic searches were conducted in PubMed/MEDLINE, Scopus, Web of Science, and Google Scholar. School-based or population-based cross-sectional studies reporting malocclusion prevalence in children aged 10–12 years were included. Extracted data comprised study characteristics, diagnostic criteria, prevalence rates, sagittal molar relationships, and occlusal traits. Risk of bias was assessed using criteria appropriate for prevalence studies. Due to methodological heterogeneity, a narrative synthesis was performed. Results Four cross-sectional epidemiological studies from India, Turkey, and Iraq were included, representing 6,444 children. Reported malocclusion prevalence ranged from approximately three-quarters to more than four-fifths of the study populations. Angle’s Class I malocclusion was consistently the most prevalent sagittal pattern, followed by Class II, while Class III was the least common. Increased overjet, increased overbite, crossbite, and midline deviations were frequently observed occlusal traits. No consistent gender differences were reported. Conclusion Malocclusion affects a substantial proportion of children aged 10–12 years, predominantly presenting as dental malalignment during late mixed dentition. Early screening programs and interceptive orthodontic strategies are warranted. Future research Standardized diagnostic criteria, multicentric longitudinal designs, and uniform reporting of occlusal traits are needed to improve comparability and strengthen epidemiological evidence.